Acute and sub-chronic toxicity study of methanol leaf extract of Cardiospermum halicacabum L and Vitex negundo L in rats - Aiyalu, Rajasekaran; Govindarajan, Arulkumaran; Ramasamy, Arivukkarasu (Pharmacognosy Communications)
Cardiospermum halicacabum L and Vitex negundo L are distributed throughout the plains of India and used in traditional practice for the treatment of inflammation and rheumatic disorders. The aim of this study is to evaluate acute and sub-chronic toxicity of methanol leaf extracts of Cardiospermum halicacabum (MLECH) and methanol leaf extract of Vitex negundo (MLEVN). MLECH and MLEVN were evaluated for acute and sub-chronic toxicity in mice and rats respectively. Materials and Methods: The acute oral toxicity study was carried out as per the OECD guidelines 423 and the sub-chronic toxicity was carried out as per the guidelines set by OECD 407 with slight modification. Body weight, food consumption, water consumption, hematological parameters, biochemical parameters, organ weight and histopathological analysis were carried out. Results: No sign of toxicity viz. lethargy, jerk, convulsion and mortality was observed upto 2000 mg/kg for MLECH and MLEVN in acute toxicity test. For subchronic toxicity test, single individual (400 mg/kg) and combined doses of MLECH and MLEVN (400 mg/kg each) in equal proportion not exhibited any signs of toxicity and mortality. Conclusion: In acute oral toxicity study, the oral administration of MLECH and MLEVN in mice was found to be safe up to a dose of 2000 mg/kg and in sub-chronic toxicity study no signs of toxicity observed at a dose of 400 mg/kg in rats.
Keywords: sub-chronic toxicity; Cardiospermum halicacabum; Vitex negundo